Paclobutrazol degradation in tropical soils - Silva, Célia Maria Maganhotto de Souza; Fay, Elisabeth Francisconi; Vieira, Rosana Faria (Pesquisa Agropecuaria Brasileira, 2003)
The objective of this work was to evaluate the degradability of paclobutrazol in soil. Soil samples were collected in orchards of two main mango production regions for exportation, at Petrolina, PE and Lins, SP, Brazil. Blended bacteria cultures, isolated from the soil samples, were assessed in liquid culture medium enriched with paclobutrazol, to verify its degradative capability. Quantification of growth regulator residues by high performance liquid chromatography was performed 15 days after application of the compound, and showed that the paclobutrazol is slowly degraded and presents half-life of 95 days.